2011
DOI: 10.1108/17506161111155414
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of organisational antecedents on employee job satisfaction in a developing country

Abstract: Purpose -Increasing dynamic technological and communication net working environment today reflects to employee attitudes and behaviours with respect of their inputs. Employee motivation is an important and critical issue specifically for health organisation where they relate to patients. The purpose of this paper is to focus on the employee perception regarding procedural justices, on job training, esprit de corps, and job clarity variables towards job satisfaction in a developing country. Design/methodology/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…Moreover, job satisfaction is a key player in the study of human behavior at work and is treated as a critical challenge for management because of its effect on employee turnover and absenteeism (Abbas et al, 2014;Hartmann et al, 2014;Khowaja et al, 2005;Miller, Rutherford, and Kolodinsky's, 2008), procedural justice and on job training (Halepota and Shah, 2011;Shah, 2011) and intention to stay, organizational commitment and trust (Schreurs et al, 2015;Sourdif, 2004;Top et al, 2015;). Researchers reveal that employee job satisfaction relates to how individuals think and feel about their jobs (Alegre et al, 2016;Oliver, 1990;Randall et al, 1999;Spector, 1997) because it can impact on quality of life and overall happiness (Frey and Stutzer, 2010).…”
Section: Insert Table 1 Herementioning
confidence: 99%
“…Moreover, job satisfaction is a key player in the study of human behavior at work and is treated as a critical challenge for management because of its effect on employee turnover and absenteeism (Abbas et al, 2014;Hartmann et al, 2014;Khowaja et al, 2005;Miller, Rutherford, and Kolodinsky's, 2008), procedural justice and on job training (Halepota and Shah, 2011;Shah, 2011) and intention to stay, organizational commitment and trust (Schreurs et al, 2015;Sourdif, 2004;Top et al, 2015;). Researchers reveal that employee job satisfaction relates to how individuals think and feel about their jobs (Alegre et al, 2016;Oliver, 1990;Randall et al, 1999;Spector, 1997) because it can impact on quality of life and overall happiness (Frey and Stutzer, 2010).…”
Section: Insert Table 1 Herementioning
confidence: 99%
“…It is a feeling about a job that is determined by the difference between the amount of valued outcome that an individual receives and the outcome he feels he should receive (Halepota & Shah, 2011). It is an important attribute that is desired by organisations through their employees.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Team spirit should develop among individuals in such cases. Team spirit is positively related to job satisfaction levels of employees in a developing country (Halepota & Shah, 2011). Randall and Cote (1991) studied that group commitment evolves from social ties of individuals and with job satisfaction in an organisation.…”
Section: Job Satisfaction and Group Commitmentmentioning
confidence: 99%
“…This means that if successfully implemented, these internal marketing activities would result in the following outcomes: better job design would promote a better role fit, and role clarity (internal product) would ensure that jobs match the individual's abilities and competencies (Ahmad et al, 2012;Halepota & Shah, 2011;Turkyilmaz et al, 2011). Mac and Shirley (2015) concur by arguing that the understanding of internal marketing needs to be "a planned effort using a marketing like approach to overcome organisational resistance to change and to align, motivate and inter functionally co-ordinate and integrate employees towards the effective implementation of corporate and functional strategies in order to deliver customer satisfaction through a process of creating motivated and customer-orientated employees" Grayson and Sanchez-Hernandez (2010) state that the integration and coordination (internal distribution) across functions, as well as more participative leadership styles (internal people), would reduce service failures because operations and functions would be better coordinated and aligned with customers' needs and behaviours during the encounter.…”
Section: Internal Marketing and Employee Satisfactionmentioning
confidence: 99%
“…The internal marketing mix elements, namely internal product, internal price, internal promotion, internal distribution, internal people, internal process and internal physical evidence (Burin, 2011) were used in this study as each element addresses the identified employee satisfaction predictors adopted. These satisfaction predictors are reward and recognition (including salary and benefits), career advancement (promotional opportunities), work environment (including personal safety), leadership, relationship with supervisors/managers, relationship with co-workers, stress and pressure, role clarity and fit, empowerment, training and development, feedback, decentralised decision-making, sharing of knowledge and information, and organisational culture (Ahmad, Wasay & Malik, 2012;Halepota & Shah, 2011;Turkyilmaz, Akman, Ozkan & Pastuszak, 2011). The theories grounding the study, the different internal marketing mix elements and their link to employee satisfaction are discussed below.…”
Section: Theoretical Frameworkmentioning
confidence: 99%